论古代叙事文学中的“纲领性预叙”现象 ：以《醒世姻缘传》为讨论中心 = On master prolepsis phenomenon of ancient Chinese narrative works : focus on Xingshi Yinyuan Zhuan - 林琳 Lin, Lin (2019)
学术界对“预叙”的研究一般集中在“局部预叙”，对具有提纲挈领之效的“纲领性预叙” 相对忽视。本文通过梳理历代叙事文学中的“纲领性预叙”现象，尝试建立对“纲领性预 叙”的认识，强调它对把握作品整体的重要意义。本文以《醒世姻缘传》为考察中心， 说明“纲领性预叙”对主题思想的呈现和人物命运的揭示所起到的总纲作用，并以《金瓶 梅》与《红楼梦》为参照，比较分析三者的异同，探讨不同的“纲领性预叙”方式、形式 和修辞，以扩充对“纲领性预叙”的认识。本文尝试总结“纲领性预叙”的三个特点与其叙 事意义。 The academic studies on prolepsis have always focused on those that only predicts one to two characters or plots, which has almost neglected the phenomena of prolepsis that plays a master role in portend for the theme of the novel and the fate of individual characters. Through an overview of master prolepsis phenomena in ancient Chinese narrative works, this paper aims to establish a general understanding on master prolepsis and emphasizes its significance in taking a firm grasp of narrative work as a whole. In this paper, Xingshi Yinyuan Zhuan is studied to verify its master prolepsis in unraveling the theme of the novel and the future development of characters. Furthermore, to gain a deeper understanding of master prolepsis, Jin Ping Mei and The Story of the Stone are used as a reference to compare the similarities and differences among the three novels, in terms of their ways, forms and rhetoric. Lastly, the thesis uncovers three characteristics of master prolepsis and its narrative significance.